Innovative NGO Strategies for Poverty Alleviation in CommunityDevelopment - Roseline, G; Amala Thanka Kumari, J (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
Poverty has been a significant problem to socio-economic development especially in the developing countries whereby major portions of the population have lacked access to basic resources and opportunities. By putting efforts on empowerment, participation and sustainability, Community development has come out as an efficient way of countering poverty. Here, the Non-Governmental Organization (NGOs) has a significant role in the change process of the society because of their presence at the grassroots level, flexibility, and people focus. In this paper, the researcher will analyze the innovative approaches that have been embraced by the NGOs with regard to finding a solution to poverty using community development approaches. The study analyzes and describes different areas of interventions including livelihood production, skill-building, microfinance, education, healthcare, women empowerment, and application of digital technologies in an analytical and descriptive manner. The long term impact is also emphasised in the paper by the importance of community participation and sustainable development practices in ensuring that the impact is long term. In addition, it explains the difficulties of NGOs and the necessity condition of cooperation between government bodies and civil societies. The paper has reached a conclusion that emerging and participatory strategies in NGO will be required to realize sustainable poverty reduction and comprehensive community growth.
Keywords: Non-Governmental Organisations (NGOs); Poverty Alleviation; Community Development; Innovation; Sustainable Development; Social Empowerment